Evolving Human Resource Landscape of the Indian Retail Sector : Bridging the Skill-Gap - Tripathi, Shruti; Gautam, Shalini; Lal, Ankur (Prabandhan: Indian Journal of Management, 2017)
The proliferation of the Indian retail sector has been remarkable. The growth chart of this industry has intensified in the last two decades and is expected to ascend even more in the future with emerging formats and international shopping experiences. As the retail industry grows leaps and bounds in India, the demand for a trained /skilled workforce augments and poses a huge challenge in front of the retail organizations. Skill shortage has become a point of concern for the employers, government agencies alike. Skilling of Indian youth has, therefore, become the foremost agenda of the industry, government, and academia. The present paper captured the workforce scenario of the Indian retail sector with specialÂ emphasis on the existing skill-gaps. Various efforts of the stakeholders to tackle the issue of skilling the employable youth are also highlighted.